Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
It is pretty long, hope you understand
x+y+z=6
+
2x-y+z=3
-------------
3x+2z=9
->3x=9-2z (1)
3x-z=0
3x=z (2)
From (1)+(2)-> z=9-2z
solve for z
-3z=9
z=-3 (3)
plug (3) in (2)
->3x=-3
->x=-1 (4)
Plug (3) and (4) in x+y+z=6
-3+y+(-3)=6
solve for y
y-6=6
->y=12
Answer:
x=-1
y=12
z=-3
x+y+z=6
+
2x-y+z=3
-------------
3x+2z=9
->3x=9-2z (1)
3x-z=0
3x=z (2)
From (1)+(2)-> z=9-2z
solve for z
-3z=9
z=-3 (3)
plug (3) in (2)
->3x=-3
->x=-1 (4)
Plug (3) and (4) in x+y+z=6
-3+y+(-3)=6
solve for y
y-6=6
->y=12
Answer:
x=-1
y=12
z=-3
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.